LITERATURE REVIEW ARTICLE : AKTIVITAS TRITERPENOID SEBAGAI SENYAWA ANTIINFLAMASI - Mutiara Insani; Himyatul Hidayah; Icha Nurfirzatulloh; Rifka Adya Shafira (Jurnal Ilmiah Wahana Pendidikan, 2023)
Triterpenoids are terpenoid-derived secondary metabolite compounds, triterpenoid class compounds show significant pharmacological activity, one of which is anti-inflammatory. This article review aims to determine the anti-inflammatory effects of triterpenoid compounds in several plants by conducting literature studies of various research results through electronic databases such as ScienceDirect, Google Scholar and PubMed. Based on the results of the literature study that has been carried out, information is obtained that the Javanese waru bark plant, butoh keling sea cucumber, bangun-bangun leaves, karas leaves, dragon lime, kecombrang flowers, star fruit leaves, and keledang leaves have anti-inflammatory activity using the in silico method, in vitro with UV-Vis spectrophotometer, in vivo in rat and mice test animals, and In vitro with Protein Denaturation Inhibition Test Method Using UV-Vis Spectrophotometer.